Effects of the online game on self- development behavior and satisfaction among nursing students in a private university - Chonsawat, Chonticha; Tongvichean, Sulee; Dangraksa, Pornpen (Thai Journal of Nursing, 2023)
The purpose of this quasi-experimental research was to evaluate effects of online game on self-development behavior and satisfaction among nursing students in a private university. A sample of 89 nursing students was purposively selected. The research tools were the online game, self-development behavior assessment and a questionnaire on satisfaction toward online game. The content validity of research tools were 0.85 and 0.80 -1.00 respectively. The reliability coefficients of self-development behavior assessment and a questionnaire on satisfaction toward online game, were 0.94 and 0.95 respectively. Descriptive statistics and paired t-test were used in data analysis. The results revealed that after the experiment, nursing students’ self-development behavior was higher than the pre-experiment at p < .01. Their satisfaction toward the online game were at the high level.